Right to education: Investing for a bright future - Rao, P. Mohan; Murthy, C.G.K. (2010)
Improvements in the education system in India have been tardy mainly due to uneducated parents, on unaffordable education system and inadequate schooling facilities. The Right to Education Act 2009 envisages quality and compulsory education to all children and to equip them with knowledge, skills and values to make them enlightened citizens. In order to achieve the objectives of the Act we need to review our standards and objectives. Without upgrading the present standards and competencies of the teachers and without providing the required infrastructure and facilities it is well nigh impossible to realise the dream of universal education. The specific provisions for disadvantaged groups, such as child labourers, migrant children, children with special needs, or those who have a disadvantage owing to social, cultural, economical, geographical, linguistic, gender or such other factors instil a ray of hope for the future. - Reproduced.
Keywords: Educational systems - India; Right to education - India; Right to education